If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7m + -3 = 3m + 17 Reorder the terms: -3 + 7m = 3m + 17 Reorder the terms: -3 + 7m = 17 + 3m Solving -3 + 7m = 17 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. -3 + 7m + -3m = 17 + 3m + -3m Combine like terms: 7m + -3m = 4m -3 + 4m = 17 + 3m + -3m Combine like terms: 3m + -3m = 0 -3 + 4m = 17 + 0 -3 + 4m = 17 Add '3' to each side of the equation. -3 + 3 + 4m = 17 + 3 Combine like terms: -3 + 3 = 0 0 + 4m = 17 + 3 4m = 17 + 3 Combine like terms: 17 + 3 = 20 4m = 20 Divide each side by '4'. m = 5 Simplifying m = 5
| 4+10x=(x+9)4 | | x-5=20/5 | | 5x-1=-51 | | 9x+13=2x+174 | | t^3-5t^2+4t=0 | | -8+2x=-16 | | 12-7x=69-28x | | -4.9x^2+22t+42=0 | | 47+0.5x= | | -3-x=-1 | | 3+2x=-11 | | -5x-7=48 | | 1-4x=-11 | | 9(X-2)*2(2X-1)=8 | | 0.3x-0.5(2x+7)=-0.8(x+2) | | 6+9+x=29 | | 4x+1=11x-85 | | 5x^2-30x+225=0 | | 6+7+x=29 | | -8x-12=6x-4(3x-1) | | 2(3x-4)=8(2x+1) | | 11+7+x=35 | | 2X-X=20 | | 4+247=13-5 | | 230-6x=30x+18 | | 9-10=61-38x | | -7(-5p+4a)= | | 3x+4=52 | | 4(x+2)=2(2x+1)+6 | | f(x)=-x^3-2 | | 1.25+6x= | | 6.95-(1.95+0.10x)=0 |